Inovasi Manajemen Pembelajaran Coding dan AI untuk Meningkatkan Literasi Digital Siswa Sekolah Dasar - Saqjuddin, Saqjuddin; Aba, Akbar; Aopmonaim, Nur Haizah (Manna wa Salwa Foundation (Yayasan Manna wa Salwa), 2025)
The transformation of education in the digital era has driven the integration of technology into the learning process, including the introduction of coding and artificial intelligence (AI) at the elementary school level. Digital literacy is now an essential skill that students must acquire early on to face the challenges of the Fourth Industrial Revolution and the society 5.0 era. This study aims to explore innovative management practices in the implementation of coding and AI learning and their impact on improving digital literacy among elementary school students. A qualitative approach with a case study design was used, involving several elementary schools in Indonesia. Data were collected through direct observation of classroom activities, interviews with teachers and school principals, and analysis of documents related to educational policies and curriculum. The findings indicate that integrating coding and AI learning can effectively enhance students' critical thinking, creativity, and problem-solving skills. However, several obstacles hinder implementation, including limited infrastructure, teachers’ lack of technological competence, and resistance to change. Therefore, innovative and collaborative learning management, as well as supportive policies, are essential to ensure the sustainability of this program in improving digital literacy among elementary school students.